Philippines teachers' beliefs on digital teaching competence in post-pandemic recovery: Still prefer online? - Tyzl N. Alcontin (Journal of Educational Management and Instruction (JEMIN), 2021)
As the effect of school closure following the coronavirus lockdowns, the use of virtual classrooms has extremely rocketed to replace face-to-face school interaction. This change has resulted in new habits and adaptation in methods and approaches of teaching, particularly in the era of post pandemic recovery. This study is based on the phenomena occurred in most of school environments where digital (online) teaching practices become a new habit for teachers and students. A question that may arise is â€œdo they still prefer online after the pandemic?â€ Drawing on this issue, this study aims to examine the beliefs of Philippines junior high schools teachers on digital teaching competence and to explore their preferences on teaching methods (online or offline) in post pandemic recovery. This study utilized a discovery-oriented qualitative approach, bridging into personal narrative and ethnographic perspective by involving twelve teachers teaching at several junior high schools in Davao Philippines. The results revealed that the teachersâ€™ beliefs mattered in terms of digital platforms (tools) and classroom activities. The results further depicted that their acquisition of digital teaching competence greatly depended on teacher professional development programs and individual trainings. Moreover, this study also discussed the teachersâ€™ preferences on the model of teaching either online or offline after the schools is opened. The results of this study contribute to providing valuable insights into redefining the situation of teaching and learning process in the era of post pandemic recovery.